2016
DOI: 10.4103/1658-631x.188247
|View full text |Cite
|
Sign up to set email alerts
|

Delivering pulmonary rehabilitation for patients with chronic obstructive pulmonary disease at home using telehealth: A review of the literature

Abstract: Pulmonary rehabilitation is recommended to restore chronic obstructive pulmonary disease (COPD) patients’ abilities to the highest level of independency and functionality. Telehealth has the potential to improve rehabilitation programs and to enhance patients’ participation. However, little is known about the potential benefits of using telehealth in providing rehabilitation for COPD patients at home. The purpose of this review was to provide a narrative synthesis of literature of studies, which use telehealth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…To the best of our knowledge, this will be the first systematic review estimating acceptance, adherence, and dropout rates of COPD populations participating in telehealth, as well as the associated factors influencing these rates. Previous systematic reviews were unable to provide information about effective elements contributing to better acceptance, adherence and dropout rates using meta-regression analysis; in contrast, the current study will try to explore elements of telehealth that impact acceptance, adherence and dropout rates 27 28. Our systematic review will analyse the literature using meta-analysis, and in doing so provide the advantage of having an opportunity to investigate and understand the correlation between pertinent factors and acceptance, adherence and dropout rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this will be the first systematic review estimating acceptance, adherence, and dropout rates of COPD populations participating in telehealth, as well as the associated factors influencing these rates. Previous systematic reviews were unable to provide information about effective elements contributing to better acceptance, adherence and dropout rates using meta-regression analysis; in contrast, the current study will try to explore elements of telehealth that impact acceptance, adherence and dropout rates 27 28. Our systematic review will analyse the literature using meta-analysis, and in doing so provide the advantage of having an opportunity to investigate and understand the correlation between pertinent factors and acceptance, adherence and dropout rates.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that telehealth may be a useful tool for minimising hospital admissions due to respiratory exacerbations, particularly in the case of individuals who are constrained by geographical barriers, or have limited access to healthcare services 5 10. Clinical trials have shown that individuals with COPD have positive attitudes towards participating in telehealth and that telehealth can promote patients’ independence toward self-management 11–17. However, the precise impact of telehealth on avoiding exacerbation and reducing hospital readmissions remains inconclusive 5.…”
Section: Introductionmentioning
confidence: 99%
“…While telerehabilitation is the use of telehealth to provide rehabilitation services such as physiotherapy, occupational therapy, speech therapy, and respiratory therapy to patients remotely ( Tang et al, 2012 ). Multiple PR modalities, such as pursed-lip breathing technique training, supervised cardiopulmonary exercise, and disease-related education sessions could be provided via telecommunication technology for patients at home ( Almojaibel, 2016 ).…”
mentioning
confidence: 99%
“…Using TH in COPD management has been found feasible, valuable, and accessible, but recent evidence shows variation regarding the completion of such interventions [ 11 , 12 , 13 ]. Previous clinical trials show that individuals with COPD have positive attitudes toward participating in TH interventions [ 14 , 15 , 16 , 17 , 18 , 19 ]. However, evidence about the impact of TH on health service outcomes or patient-related outcomes is still inconclusive [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%